2007
DOI: 10.1002/chin.200802122
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: 1,3‐Dipolar Cycloadditions. Part 14. Highly Selective Cycloadditions of C,N‐Diaryl Nitrones to Diethyl Aryl Methylene Malonates.

Abstract: Isoxazole derivatives R 0240 1,3-Dipolar Cycloadditions. Part 14. Highly Selective Cycloadditions of C,N-Diaryl Nitrones to Diethyl Aryl Methylene Malonates. -1,3-Dipolar cycloaddition of nitrones (I) to arylmethylenemalonates (II) occurs with complete regio-and diastereoselectivity to furnish trans-3,5-diarylisoxazolidines (III). This is in contrast to nitrone cycloaddition reactions with cinnamic acid derivatives, which provide two diastereomeric cycloadducts. -(BANERJI*, A.; SENGUPTA, S.; NAYAK, A.; BISWAS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The arylidene malonate dipolarphiles (18,19,20) were prepared by standard experimental procedures [24][25][26] from diethyl malonates by condensation with the appropriate aromatic aldehydes in presence of piperidine in benzene solution. The structural integrities of the dipolarophiles were confirmed by IR and NMR spectra.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The arylidene malonate dipolarphiles (18,19,20) were prepared by standard experimental procedures [24][25][26] from diethyl malonates by condensation with the appropriate aromatic aldehydes in presence of piperidine in benzene solution. The structural integrities of the dipolarophiles were confirmed by IR and NMR spectra.…”
Section: Methodsmentioning
confidence: 99%
“…The 32CA of four differently substituted nitrones (1)(2)(3)(4) to various substituted methyl E-cinnamates are reported (Scheme-I). Additionally, the reaction of C-(4-nitrophenyl)-N-(4′-chlorophenyl) nitrone (14) with 8, reported earlier [19], was repeated to obtain further amounts of the resultant cycloadducts 15a-c.…”
Section: Ca Of Cn-diaryl Nitrones To Substituted Methyl Ecinnamatesmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases cycloaddition of azomethine ylides with carbonyl double bond was reported as a side reaction, and not as a synthetic procedure on its own [31]. Our longstanding interest in 1,3-dipolar cycloaddition [41][42][43][44][45] led us to turn our attention on the direct synthesis of oxazolidine moieties by cycloaddition of non-stabilised azomethine ylides with carbonyl compounds. Orsini et al [32] and Felluga et al [33] had reported direct cycloaddition of azomethine ylides with carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%